Perspectives of rural carers on benefits and barriers of receiving occupational therapy via Information and Communication Technologies. (26th January 2016) - Gardner, Kate; Bundy, Anita; Dew, Angela
Abstract : Introduction: People with a disability living in rural areas commonly experience difficulty in accessing therapy services. Information and Communication Technologies (ICT) may have the potential to provide occupational therapy services remotely through two‐way visual interactions. The aim of this qualitative study was to understand the perspectives of carers of a person with a disability living in rural New South Wales (NSW) on the use of ICT for occupational therapy service delivery. Methods: Individual semi‐structured telephone interviews were conducted with 11 carers of persons with a disability living in rural NSW. Participants were asked about their use of technology, therapy experiences and their attitudes towards using ICT to receive occupational therapy for their son/daughter. Data were analysed via constant comparison and thematic analysis. Results: Participants were willing to use ICT to enhance their current access to therapy based on their in‐depth knowledge of their son or daughter and their prior experiences with therapy and technology. For ICT to work for occupational therapy, participants identified the need for support and access prior to, during and between ICT sessions. Conclusion: From the carers' perspectives, ICT has the potential to increase access to occupational therapy services for people with a disability who live in rural NSW. Occupational therapists could benefit from eliciting the experiences, knowledge and willingness of rural carers to deliver therapy via ICT, thereby supplementing and enhancing in‐person service delivery.